2023
DOI: 10.1021/acsami.3c00101
|View full text |Cite
|
Sign up to set email alerts
|

Cubosome Lipid Nanocarriers As a Drug Delivery Vehicle for Intracellular Mycobacterium tuberculosis Infections

Abstract: Mycobacterium tuberculosis (MTB) causes the infectious disease tuberculosis (TB), responsible for more deaths than any other single infectious disease in history. Intracellular MTB are slow growing and difficult to target with traditional antitubercular drugs, leading to the emergence of multidrug resistance in TB infection, which is a major global public health issue. Recent advances in innovative lipid nanotechnologies for drug delivery have demonstrated promising outcomes for chronic infectious diseases but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Among them, drug carriers made of modified mannose are the most common and can be added to liposomes, SLN, and polymer micelles [255][256][257] Studies have shown that cubosomal lipid nanocarriers exhibit higher drug delivery efficiency as well as bioavailability than conventional formulations. They are not only effective against free bacilli but also have the ability to deliver drugs to intracellular bacilli [258]. Thus, the identification of better sets of ligands with higher binding affinity for macrophage-based receptors might result in enhanced targeting efficiency.…”
Section: Targeted Therapymentioning
confidence: 99%
“…Among them, drug carriers made of modified mannose are the most common and can be added to liposomes, SLN, and polymer micelles [255][256][257] Studies have shown that cubosomal lipid nanocarriers exhibit higher drug delivery efficiency as well as bioavailability than conventional formulations. They are not only effective against free bacilli but also have the ability to deliver drugs to intracellular bacilli [258]. Thus, the identification of better sets of ligands with higher binding affinity for macrophage-based receptors might result in enhanced targeting efficiency.…”
Section: Targeted Therapymentioning
confidence: 99%
“…The fusion absorption method described facilitates the effective and expeditious internalization of cubosomes by Gram-negative bacteria, even when they encounter their tough outer membrane. The cubosomal formulations have been utilized in enhancing the antibacterial activity of some antibiotics, including gatifloxacin [ 33 ], erythromycin [ 34 ], and rifampicin [ 35 ].…”
Section: Introductionmentioning
confidence: 99%